Common diagnoses among pediatric attendances at emergency departments - Shuen Yin Celine Yoong; Peck Har Ang; Shu-Ling Chong; Yong-Kwang Gene Ong; Nur Diana Bte Zakaria; Khai Pin Lee; Jen Heng Pek (BMC, 2021)
Abstract Background Pediatric patients present to Emergency Departments (EDs) with a variety of medical conditions. An appreciation of the common presenting conditions can aid EDs in the provision of pediatric emergency care. In this study, we established the common pediatric diagnoses seen at the general EDs, with reference to a pediatric ED. Methods A retrospective review of medical records was performed for patients less than 16 years old at a pediatric ED and two general EDs from 1 January to 31 December 2018. Information including patient demographics, triage category, case type and diagnoses were collected. Results There were 159,040 pediatric attendances, of which 3477 (2.2%) were seen at the general EDs. Non-traumatic conditions were most prevalent at both general (N = 1933, 55.6%) and pediatric (N = 128,415, 82.5%) EDs. There was a higher proportion of trauma related conditions seen at the general EDs (N = 1544, 44.4%) compared to the pediatric ED (N = 27,148, 17.5%; p < 0.01). Across all EDs, upper respiratory tract infection, unspecified musculoskeletal pain and gastroenteritis were the three most common non-trauma related diagnoses, while fracture, wound and contusion were the three most common trauma related diagnoses. There was a greater proportion of emergent (P1) cases seen at the general EDs (N = 233, 6.7%) than the pediatric ED (N = 3821, 2.5%; p < 0.01). Respiratory conditions including bronchiolitis, asthma and bronchitis were the most common emergent (P1) diagnoses. Conclusions The common diagnoses among pediatric attendances varied between pediatric and general EDs. Therefore, general EDs should focus their efforts on these common diagnoses, especially the emergent (P1) ones, so that they can enhance their preparedness and work towards providing quality pediatric emergency care.